A Simulation of Fuzzy Logic Based Fuel Control Unit on Aircraft Engine System - A Ramaniya; Suprijadi Suprijadi (Pusat Teknologi Instrumentasi dan Otomasi (PTIO) - Institut Teknologi Bandung, 2009)
Gas turbine engine plays an important role in many technical area such as aviation engine and power turbine generator. The basic fundamental of this engine is to maintain stability of the engine rotation speed(RPM) during all cycle of engine operation. To control the rpm, a Fuel Control Unit is installed. This device controls the rpm and also the fuel flow consumption through a fuel injector in the combustion chamber. In the past decade, the pneumatic fuel control unit is starting to be replaced by electronic fuel control unit. An electronic fuel control unit is believed to have better performance compared to pneumatic controllers. In this paper, a simulation of a fuzzy logic based fuel control unit on Allison Bendix 250 engine was done using MATLAB 7.0. From this simulation, it can be observed that the fuzzy logic based fuel control unit was able to stabilize the engine under disturbances. Results of this simulation will be discussed in this paper. Keywords: Gas Turbine Engine, Allison Bendix 250, Fuzzy Logic, Fuel Control Unit, RPM, Fuel Flow.